Entre o consumo e a comercialização: economia solidária e o consumo responsável como alternativas ao supermercadismo - Paganotto, Gabriela Batista (Universidade Federal de São Carlos, 2025)
The supermarket monopoly has been steadily expanding. Aligned with neoliberal logic and agribusiness, this commercialization model brings numerous negative social impacts, such as power asymmetries that exploit producers and the transformation and standardization of global food systems in the pursuit of absolute profit maximization. As the power of these networks grows, short commercialization circuits are weakening, and family farmers often find themselves marginalized by hegemonic commercialization structures. In this context, this study seeks to understand solidarity economy and responsible consumption as alternative modes of production and commercialization that place agroecological production at the forefront of consumption relations, while also promoting agroecological practices that prioritize social well-being and sustainability. To this end, interviews were conducted to capture the perspectives of responsible consumers and settled women producers regarding the establishment of direct and humanized commercialization relationships. The results revealed that the path toward building a solidarity network is long, but the existing initiatives highlight the potential and possibilities for constructing an alternative model to the supermarket hegemony.
Between consumption and commercialization: solidarity economy and responsible consumption as alternatives to supermarketization
Keywords: Agricultura familiar; Agroecologia; Comercialização; Consumo responsável; Economia Solidária; CIENCIAS HUMANAS::SOCIOLOGIA